Knowledge and Prescribing Practice of Periconceptional Folic Acid And Associated Factors Among Health Professionals in Bole Sub City, Addis Ababa, Ethiopia: Knowledge and Prescribing Practice of Periconceptional Folic Acid - Demissie, Dereje; Muluye, Hana (Ethiopian Journal of Reproductive Health, 2026)
Background: Proper utilization of folic acid supplementation is crucial for preventing defects, which affect approximately 200,000 neonates annually. Folic acid supplementation is crucial for disease prevention and requires effective health communication and incorporation of folic acid-enriched food items into daily diets. Health professionals must be updated on folic acid doses and prescription practices to prevent these defects in pregnant women and neonates. Objective: This study aimed to assess the knowledge and prescribing practice of periconceptional folic acid use and associated factors among health professionals in Bole Sub City, Addis Ababa, Ethiopia 2024. Materials and methods: This study was conducted in Bole Sub-city, one of the 11 sub-cities in Addis Ababa, Ethiopia. This subcity is bounded by Yeka, Kirkos, Nifas Silk-Lafto, Akaky Kaliti, and Lemi Kura. Descriptive statistics, such as frequency and percentage, were used to summarize the results, and binary logistic regression was used to describe the association between variables. Statistical significance was set at p < 0.05. Result: The complete response rate was 96.4%. This study determined that a nearly equal number of participants had good and poor knowledge about periconceptional folic acid use, and also this study determined that 60.6% of healthcare professionals had poor prescribing practices of periconceptional folic acid in the study area. Professional background nurses (AOR = 2.84, 95% CI: 1.44-5.6), public health professionals/others (AOR = 4.26, 95% CI: 1.98-9.4), previously employed nongovernmental organization(NGO health care workers (AOR = 2.52, 95% (1.34 4.74), had worked in an antenatal care (ANC) clinic (AOR = 2.2, 95% CI: 1.07-4.53), had ever taken training on folic acid (AOR = 2.85, 95% CI: 1.4-5.78), and had ever attended training on neural tube defects (NTDs) (AOR = 12.6, 95% CI: 5.8-27.35). Conclusion and Recommendation: This study determined that Nearly half of the study participants had good knowledge about periconceptional folic acid use, with identified factors that increased the odds of having good knowledge about periconceptional folic acid use: professional background nurses, public health professionals/others, previously employed NGO health care workers who had worked in an ANC clinic, had received training on folic acid, and had attended training on neural tube defects (NTDs).